Limited Evidence of Associations Between Executive Functioning and Alcohol Involvement In UK Adolescents. (9th April 2021) - Burton, Sam; Puddephatt, Jo-Anne; Baines, Laura; Sheen, Florence; Warren, Jasmine G; Jones, Andrew
Abstract: Aims: Deficits in motor inhibitory control and working memory have been hypothesized to be both a cause and consequence of heavy alcohol use. Adolescence is a critical developmental stage for inhibitory control and working memory, and it is also a stage when individuals are most likely to initiate alcohol use. This study aimed to examine whether inhibitory control and working memory would predict alcohol use and involvement in a group of UK adolescents. Methods: We recruited 220 ( N  = 178, female) adolescents, aged between 16 and 18, from eight higher education settings in the Merseyside region of the UK. Alcohol use was examined using the Timeline Follow-Back and involvement (and related problems) using the Adolescent Alcohol Involvement Scale. A reward-based inhibitory control task (Go/No-Go) was used to examine the inhibition and reward sensitivity, and a self-ordered pointing task was used to measure working memory. Results: Multiple regression demonstrated that neither inhibitory control ( b  = 0.02 (95% confidence interval (CI): −0.21, 0.24)) nor working memory ( b  = −0.12 (95% CI: −0.30, 0.07)) were significant predictors of alcohol use (units consumed). Inhibitory control ( b  = 0.61 (95% CI: 0.12, 1.09), specifically, in the no reward condition and school deprivation ( b  = 0.67 (95% CI: 0.06, 1.28) significantly predicted alcohol-related problems. Conclusions: Our findings demonstrated limited evidence that deficits in specific mechanisms of executive functioning (i.e. motor inhibition and working memory) were associated with alcohol-related problems in UK adolescents. This study adds to an increasing body of literature suggesting weak or non-existent links between inhibitory control, working memory and alcohol use.